2011
DOI: 10.1007/s13361-010-0016-5
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet Photodissociation of Carboxylate-Derivatized Peptides in a Quadrupole Ion Trap

Abstract: The fragmentation patterns obtained by ultraviolet photodissociation (UVPD) and collisioninduced dissociation (CID) in a quadrupole ion trap mass spectrometer were compared for peptides modified at their C-termini and at acidic amino acids. Attachment of Alexa Fluor 350 or 7-amino-4-methyl-coumarin chromophores at the C-terminal and acidic residues enhances the UV absorptivity of the peptides and all fragment ions that retain the chromophore, such as the y ions that contain the chromophore-modified C-terminus.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…178185 In contrast to the bond-specific cleavages promoted by UVPD described above, in this case a chromophore is attached to the molecule of interest via a covalent tagging reaction for a different purpose. The tagging reaction appends a chromophore that endows the molecules with high photoabsorption cross-sections not exhibited by the non-tagged molecules.…”
Section: Applications Of Ultraviolet Photodissociation For Biologimentioning
confidence: 99%
See 2 more Smart Citations
“…178185 In contrast to the bond-specific cleavages promoted by UVPD described above, in this case a chromophore is attached to the molecule of interest via a covalent tagging reaction for a different purpose. The tagging reaction appends a chromophore that endows the molecules with high photoabsorption cross-sections not exhibited by the non-tagged molecules.…”
Section: Applications Of Ultraviolet Photodissociation For Biologimentioning
confidence: 99%
“…The requirement for a suitable chromophore can be exploited strategically in wavelength-selective, chromophore-specific applications, as reported in several recent applications. [178][179][180][181][182][183][184][185] In contrast to the bond-specific cleavages promoted by UVPD described above, in this case a chromophore is attached to the molecule of interest via a covalent tagging reaction for a different purpose. The tagging reaction appends a chromophore that endows the molecules with high photoabsorption cross-sections not exhibited by the non-tagged molecules.…”
Section: Chromophore-selective Uvpdmentioning
confidence: 99%
See 1 more Smart Citation
“…An interesting alternative fragmentation method explored is surface induced dissociation (SID). Noteworthy, SID was shown to produce preferably symmetric charge partitioning for protein assemblies, which was attributed to its more prompt, high-energy fragmentation mechanism. ,, Another newcomer in the field of protein assembly dissociation techniques is ultraviolet photodissociation (UVPD), which utilizes the natural chromophores present in the backbone of peptides and proteins to absorb highly energetic photons (λ = 193 nm) emitted from a laser. The technique may provide prompt fragmentation at an activation time scale close to the energy deposition in SID, and could thus potentially prove to be a beneficial method for probing of assembly composition and topology. In this study, we report the modification of an Orbitrap-based mass spectrometer with Extended Mass Range (EMR) capabilities to support UVPD.…”
Section: Introductionmentioning
confidence: 99%
“…In a pioneering study, N‐terminal attachment of dinitrophenyl on amino acids and small peptides allows fragments to be produced upon photoexcitation by 333–365 nm and 454–514 nm photons . Other studies have been reported that illustrate the strategy of attaching chromophores to molecules at the N‐ or C‐terminus (and acidic residues) in order to increase their light absorption properties at 355 or 351 nm . Fragmentation patterns were also simplified significantly, exhibiting only b ions, thus allowing de novo peptide sequencing to be improved.…”
Section: Chromophore‐derivatized Amino Acid Specific Lidmentioning
confidence: 99%